2007
DOI: 10.1080/08982100701527981
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Liposome Performance and Evaluation: Lessons from the Development of Vescan

Abstract: In the early 1980s, Vestar Inc., a company founded on the basis of science developed by the California Institute of Technology and the City of Hope, brought into development an imaging agent based on liposome encapsulated (111)In(3+). This agent, named Vescan, together with the gamma ray perturbed angular correlation spectroscopy technique to examine liposome integrity, was envisioned as a broadly applicable in vivo tumor diagnostic agent. While not ultimately commercialized, the agent was used to successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…These studies demonstrated that permeability rates depended on molecular or particle properties such as hydrodynamic diameter and shape (4). Liposomal imaging agents based on single-photon emission computed tomographic (SPECT) or positron emission tomographic (PET) imaging have been examined as well (20)(21)(22). A widely studied class of imaging agents is superparamagnetic iron oxide nanoparticles, which have excellent MRI contrast characteristics and demonstrate concentration-related negative contrast on T2-and T2 Ã -weighted sequences.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrated that permeability rates depended on molecular or particle properties such as hydrodynamic diameter and shape (4). Liposomal imaging agents based on single-photon emission computed tomographic (SPECT) or positron emission tomographic (PET) imaging have been examined as well (20)(21)(22). A widely studied class of imaging agents is superparamagnetic iron oxide nanoparticles, which have excellent MRI contrast characteristics and demonstrate concentration-related negative contrast on T2-and T2 Ã -weighted sequences.…”
Section: Introductionmentioning
confidence: 99%
“…With their half-life of, respectively, 6 h and 2.8 days, 99m Tc and 111 In are well suited to monitor the fate of liposomes in vivo using SPECT imaging, since liposomes usually have a half-life of less than 24 h in rodents and 48 h in humans [64][65][66][67]. The only liposome-based radiotracer formulation that was used in late-stage clinical trials was a liposomal formulation radiolabeled with 111 In, which was enabled by incorporation of the ionophore A23187 in the lipid bilayer and encapsulation of NTA as chelator [68]. Clinical studies with this formulation showed that liposomes containing phospholipids and cholesterol were well tolerated and that a wide variety of tumors could be imaged.…”
Section: Spect Imaging With Radiolabeled Liposomesmentioning
confidence: 99%
“…The well-known positron emitters for PET imaging, 18 F and 68 Ga, have been used successfully to radiolabel liposomes and to image different types of cancers. 18 F and 68 Ga-labeled liposomes showed stable radiolabel retention in vivo and their accumulation in tumor lesions was sufficient to visualize tumor lesions with PET imaging [80][81][82].…”
Section: Pet Imaging With Radiolabeled Liposomesmentioning
confidence: 99%
See 2 more Smart Citations